Does preoperative multidisciplinary team assessment of high-risk patients improve the safety and outcomes of patients undergoing surgery? - B. I. Kuiper; L.M.J. Janssen; K. S. Versteeg; B. L. ten Tusscher; J. I. van der Spoel; W. D. Lubbers; G. Kazemier; S. A. Loer; P. Schober; V. P. van Halm (BMC Anesthesiology, 2024)
Abstract Background International guidelines recommend preoperative multidisciplinary team (MDT) assessment for high-risk surgical patients. Preoperative MDT meetings can help to improve surgical care, but there is little evidence on whether they improve patient outcomes. Methods This paper aims to share our experience of MDT meetings for high-risk surgical patients to underline their added value to the current standard of care. An observational study of a retrospective cohort of preoperative high-risk MDT meetings of a tertiary referral hospital between January 2015 and December 2020. For 249 patients the outcomes preoperative data, MDT decisions, and patient outcomes were collected from electronic health records. Main results A total of 249 patients were discussed at high-risk MDT meetings. Most of the patients (97%) were assessed as having an American Society of Anesthesiology score ≥ 3, and 219 (88%) had a European Society of Cardiology and European Society of Anaesthesiology risk score of intermediate or high. After MDT assessment, 154 (62%) were directly approved for surgery, and 39 (16%) were considered ineligible for surgery. The remaining 56 (23%) patients underwent additional assessments before reconsideration at a high-risk MDT meeting. The main reason for patients being discussed at the high-risk MDT meeting was to assess the risk-benefit ratio of surgery. Ultimately, 184 (74%) patients underwent surgery. Of the operated patients, 122 (66%) did not have a major complication in the postoperative period, and 149 patients (81%) were alive after one year. Conclusions This cohort study shows the vulnerability and complexity of high-risk patients but also shows that the use of an MDT assessment contributes too improved peri- and postoperative treatment strategies in high-risk patients. Most patients underwent surgery after careful risk assessment and, if deemed necessary, preoperative and perioperative treatment optimization to reduce their risk.